A társadalmi tőke szerepe az orvosok érdekérvényesítésében - Gyukits, György (Szociológiai Szemle, 2024)
The study examines the role of social capital in enforcing physicians' interests. Based on an empirical sociological survey, we wanted to find an answer to the question of what is the role of the Chamber of Physicians and that of the trade union in enforcing interests after the change of the regime (1989). The findings of research have been described in the form of case studies. The case studies deal with the following themes: conflicts between the boss and the subordinate, wage disputes, winding up of workplaces, privatisation. The case studies indicate that the physicians' interpersonal relations are decisive in enforcing their interests. This can be explained by the fact that using interpersonal relations as resources is a much more efficient means for enforcing their interests than relying on an organisation.